2016
DOI: 10.1111/nph.14247
|View full text |Cite
|
Sign up to set email alerts
|

Below‐ground frontiers in trait‐based plant ecology

Abstract: Contents 1597I.1597II.1597III.1598IV.1598V.1600VI.1601VII.1601VIII.16011602References1602 Summary Trait‐based approaches have led to significant advances in plant ecology, but are currently biased toward above‐ground traits. It is becoming clear that a stronger emphasis on below‐ground traits is needed to better predict future changes in plant biodiversity and their consequences for ecosystem functioning. Here I propose six ‘below‐ground frontiers’ in trait‐based plant ecology, with an emphasis on traits gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
211
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(230 citation statements)
references
References 43 publications
(97 reference statements)
10
211
0
2
Order By: Relevance
“…A similar secondary dimension of root trait variation was recently observed in a broad range of tree species (Kramer‐Walter et al, ) and Ma et al () found that at the global level root traits do not follow the same patterns observed in above‐ground traits. Together with our observations, these results support the hypothesis that root traits are multidimensional (Weemstra et al, ), reflecting the greater potential range of root trait combinations necessary to enhance plant fitness under different environmental conditions (Bardgett, ; Laliberté, ; Laughlin, ; Zemunik, Turner, Lambers, & Laliberté, ).…”
Section: Discussionsupporting
confidence: 89%
“…A similar secondary dimension of root trait variation was recently observed in a broad range of tree species (Kramer‐Walter et al, ) and Ma et al () found that at the global level root traits do not follow the same patterns observed in above‐ground traits. Together with our observations, these results support the hypothesis that root traits are multidimensional (Weemstra et al, ), reflecting the greater potential range of root trait combinations necessary to enhance plant fitness under different environmental conditions (Bardgett, ; Laliberté, ; Laughlin, ; Zemunik, Turner, Lambers, & Laliberté, ).…”
Section: Discussionsupporting
confidence: 89%
“…Currently, plant ecologists seek to identify the multiple dimensions of fine‐root trait variation related to plant performance (Laliberté, ; Liese, Alings, & Meier, ; Valverde‐Barrantes & Blackwood, ; Wang et al, ; Weemstra et al, ). This study demonstrates that fine‐root mass and length density—in combination with fine‐root life span—can represent an additional below‐ground dimension to capture species’ variation in performance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, plant scientists have become increasingly interested in belowground functional traits such as root length, root hair and exudation of carboxylates (Laliberté, ); however, measuring these traits – for example, carboxylates in the rhizosphere – is laborious (Lambers et al ., ). Cluster roots release large amounts of carboxylates in an exudative burst to mobilize not only P, but also manganese (Mn) (Gardner et al ., ; Shane & Lambers, ).…”
Section: Introductionmentioning
confidence: 97%